2021
DOI: 10.1002/jcsm.12684
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐compartment metabolomics and metagenomics reveal major hepatic and intestinal disturbances in cancer cachectic mice

Abstract: Background Cancer cachexia is a multifactorial syndrome characterized by multiple metabolic dysfunctions. Besides the muscle, other organs such as the liver and the gut microbiota may also contribute to this syndrome. Indeed, the gut microbiota, an important regulator of the host metabolism, is altered in the C26 preclinical model of cancer cachexia. Interventions targeting the gut microbiota have shown benefits, but mechanisms underlying the host-microbiota crosstalk in this context are still poorly understoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 100 publications
(217 reference statements)
8
35
0
Order By: Relevance
“…In the last years, a number of studies focused on the possibility that altered energy metabolism could be the trigger of muscle wasting. Indeed, metabolomic analyses have shown that energy and protein metabolism are markedly perturbed in the skeletal muscle and in the liver of tumor-bearing animals [7,8]. Consistently, hypermetabolism associated with altered energy balance has been detected in about 50% of newly diagnosed cancer patients [9].…”
Section: Pathogenesis Of Cancer Cachexiamentioning
confidence: 92%
“…In the last years, a number of studies focused on the possibility that altered energy metabolism could be the trigger of muscle wasting. Indeed, metabolomic analyses have shown that energy and protein metabolism are markedly perturbed in the skeletal muscle and in the liver of tumor-bearing animals [7,8]. Consistently, hypermetabolism associated with altered energy balance has been detected in about 50% of newly diagnosed cancer patients [9].…”
Section: Pathogenesis Of Cancer Cachexiamentioning
confidence: 92%
“…Under pathological conditions of excessive adipose tissue lipolysis, the liver acts as a major sink for adipose tissue-derived FFA. Accordingly, hepatic lipids and triglycerides were elevated 3-5 fold in colon (C26) tumor-bearing mice, an effect that was not due to reduced food intake [56,74]. The hepatic steatosis could be explained by a reduction in carnitine and carnitine biosynthesis, decreased VLDL excretion, reduction in lipogenic genes, and an upregulation fatty acid transporters in the liver [56,74].…”
Section: Hyperlipidemiamentioning
confidence: 99%
“…Increased hepatic glucose output may be due to increased gluconeogenesis because increased metabolicintermediates and increased gene-expression of markers of gluconeogenesis have been observed in the liver of tumor-bearing animals [55]. A recent proton nuclear magnetic resonance (1H-NMR) metabolomics study of cachexia in the mouse colon carcinoma 26 (C26) model revealed reduced glucose metabolism and increased lipid metabolism in the liver [56]. Whether hepatic metabolic changes in cancer is induced by insulin resistance or is a contributing factor to insulin resistance remain unidentified.…”
Section: Insulin Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…Not only is predicting cachexia important, being able to monitor the progression of the condition is also essential. Microbial dysbiosis has been observed in preclinical cancer cachexia models [ 111 , 112 ], which could be a potential diagnostic reference for cancer cachexia. Enterobacteriaceae levels were increased, while a reduction of lachnospiraceae and ruminococcaceae were found in C26 cancer cachexia model [ 111 , 112 ].…”
Section: Discussionmentioning
confidence: 99%